From Competencies to Clinical Work: Entrustable Professional Activities as a Global Language for Undergraduate Medical Education - Salam, Abdus; Al Mahmood, Abu Kholdun; Satwi, Sapari; Zainol, Jamaludin (International Journal of Human and Health Sciences (IJHHS), 2026)
Abstract not available International Journal of Human and Health Sciences Vol. 10 No. 01 Jan’26 Page: 3-7